2021
DOI: 10.1007/s42773-021-00123-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochar alleviates metal toxicity and improves microbial community functions in a soil co-contaminated with cadmium and lead

Abstract: Soil amendment with biochar alleviates the toxic effects of heavy metals on microbial functions in single-metal contaminated soils. Yet, it is unclear how biochar application would improve microbial activity and enzymatic activity in soils co-polluted with toxic metals. The present research aimed at determining the response of microbial and biochemical attributes to addition of sugarcane bagasse biochar (SCB) in cadmium (Cd)-lead (Pb) co-contaminated soils. SCBs (400 and 600 °C) decreased the available concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Although the HA biochar used in our study reduced microbial activity and N availability, its high surface area, and low H:C ratio indicates it would be effective for remediating contaminated soils and improving soil health. Several studies [ 58 , 59 ] have linked enhanced soil microbial activity and crop growth to a decrease in the bioavailability of heavy metals in contaminated soils due to sorption on biochar surfaces. Other studies [ 60 , 61 ] that have documented simultaneous decrease in the bioavailability of heavy metals in contaminated soils and enhanced soil microbial activity and N availability had greater (0.6–0.9) biochar H:C ratio as compared to our study, suggesting the likely benefits of HA in contaminated soils.…”
Section: Resultsmentioning
confidence: 99%
“…Although the HA biochar used in our study reduced microbial activity and N availability, its high surface area, and low H:C ratio indicates it would be effective for remediating contaminated soils and improving soil health. Several studies [ 58 , 59 ] have linked enhanced soil microbial activity and crop growth to a decrease in the bioavailability of heavy metals in contaminated soils due to sorption on biochar surfaces. Other studies [ 60 , 61 ] that have documented simultaneous decrease in the bioavailability of heavy metals in contaminated soils and enhanced soil microbial activity and N availability had greater (0.6–0.9) biochar H:C ratio as compared to our study, suggesting the likely benefits of HA in contaminated soils.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stage, it may be that biochar can adsorb manganese ions in the soil and reduce the toxicity of manganese ions to microorganisms. The application of exogenous organic carbon increased the content of DOC [43]; the latter may be DOC can be used as a heavy metal ion carrier, so that manganese ions combined with DOC, thereby reducing the DOC content [44]. The content of ROC in the soil of the two sugarcane elds increased with the application ratio of biochar.…”
Section: Effects Of Biochar Application On Different Soil Carbon Frac...mentioning
confidence: 99%
“…Soil microorganisms may be the most sensitive soil organisms to subtle changes in the soil environment. Therefore, the toxic effect of Pb in the soil can reduce soil microbial biomass (Nahid and Fayez, 2021), inhibit microbial metabolism (Xu et al, 2021) and alter microbial community composition (Jianhua et al, 2021). Kamaruzzaman et al found that Pb exposure enhanced the Pb resistance of microorganisms; for example, Bacillus and Enterobacter were found to have high tolerance to Pb stress (Kamaruzzaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microorganisms may be the most sensitive soil organisms to subtle changes in the soil environment. Therefore, the toxic effect of Pb in the soil can reduce soil microbial biomass ( Nahid and Fayez, 2021 ), inhibit microbial metabolism ( Xu et al., 2021 ) and alter microbial community composition ( Jianhua et al., 2021 ). Kamaruzzaman et al.…”
Section: Introductionmentioning
confidence: 99%